Immunogenicity and protective efficacy of a novel bacterium-like particle-based vaccine displaying canine distemper virus antigens in mice and dogs - Jianzhong Wang; Lina Liu; Xianchun Zong; Chunliu Wang; Guangmei Zhu; Guilian Yang; Yanlong Jiang; Wentao Yang; Haibin Huang; Chunwei Shi; Yan Zeng; Nan Wang; et al. (Microbiology Spectrum, 2024)
ABSTRACTCanine distemper virus (CDV) poses a severe threat to both domesticated and wild animals, including multiple carnivores. With the continued expansion of its host range, there is an urgent need for the development of a safer and more effective vaccine. In this study, we developed subunit vaccines based on a bacterium-like particle (BLP) delivery platform containing BLPs-F and BLPs-H, which display the CDV F and H glycoprotein antigens, respectively, using the antigen-protein anchor fusions produced by a recombinant baculovirus insect cell expression system. The combination of BLPs-F and BLPs-H (CDV-BLPs), formulated with colloidal manganese salt [Mn jelly (MnJ)] adjuvant, triggered robust CDV-specific antibody responses and a substantial increase in the number of interferon gamma (IFN-γ)-secreting CD4+ and CD8+ T cells in mice. Dogs immunized intramuscularly with this vaccine not only produced CDV-specific IgG but also displayed elevated concentrations of IFN-γ and interleukin 6 in their serum, along with an increase of the CD3+CD4+ and CD3+CD8+ T cell subsets. Consequently, this heightened immune response provided effective protection against disease development and reduced viral shedding levels following challenge with a virulent strain. These findings suggest that this BLP-based subunit vaccine has the potential to become a novel canine distemper vaccine.IMPORTANCEMany sensitive species require a safe and effective distemper vaccine. Non-replicating vaccines are preferred. We constructed subunit particles displaying canine distemper virus (CDV) antigens based on a bacterium-like particle (BLP) delivery platform. The CDV-BLPs formulated with theMn jelly adjuvant induced robust humoral and cell-mediated immune responses to CDV in mice and dogs, thereby providing effective protection against a virulent virus challenge. This work is an important step in developing a CDV subunit vaccine.